Impact of Head and Neck Radiotherapy on Perioperative Airway Management in Urological Surgeries: An Anesthetic and Vascular Perspective: Dampak Radioterapi Kepala dan Leher terhadap Manajemen Jalan Napas Perioperatif pada Bedah Urologi: Perspektif Anestesi dan Vaskular - Ghiffary, Muamar; Reza, Muhammad Alfi; Sayati, Muhammad Satir; Awaluddin, Muhammad; Fauzi, Ahmad Nur (Postgraduate Program in Public Health, Universitas Muslim Indonesia, 2025)
ABSTRACT Background: Radiotherapy is a primary treatment for various types of cancer, but it can cause long-term complications, including tissue fibrosis, vascular stenosis, and urological dysfunction. These effects influence anesthetic strategies, surgical technique selection, and postoperative management. Objective: This study aims to compare the effectiveness of endovascular techniques and open vascular reconstruction in managing post-radiotherapy vascular complications, as well as to evaluate the anesthetic and urological implications of radiation-induced tissue fibrosis. Method: This study reviews literature and clinical data on the effects of radiotherapy on the vascular system, airway, and urological system. The comparison between endovascular techniques and open vascular reconstruction is analyzed based on effectiveness, complication risks, and durability. Results: Endovascular techniques offer a minimally invasive approach with faster recovery but carry a higher risk of restenosis compared to open vascular reconstruction, which provides better long-term outcomes despite greater perioperative complications. In patients with post-radiotherapy fibrosis, carotid artery and jugular vein stenosis increase the risk of stroke, while radiation-induced urethral strictures require reconstructive approaches tailored to severity. In anesthesiology, patients with airway changes due to fibrosis are more safely managed with regional anesthesia and multimodal analgesia techniques. Conclusion: The management of post-radiotherapy patients requires a multidisciplinary approach involving anesthesiology, interventional radiology, urology, and vascular surgery specialists. Combining minimally invasive techniques with more aggressive reconstructive strategies can improve clinical outcomes in patients with vascular and urological complications resulting from radiotherapy.